Evaluation of Anti-Bacterial, Analgesic and Anti-Inflammatory activities of Oncocalyxone A isolated from Prenanthes sarmentosus - Sivagnanam Ilayaraja, Kalaivanan Prabakaran, Rajamanickam Manivannan (Journal of Applied Pharmaceutical Science, 2014)
The aim of the present study was to evaluate the anti-bacterial, analgesic and anti-inflammatory activities with oncocalyxone A isolated from the leaves of Prenanthes sarmentosus. The anti-bacterial activity of different concentrations of oncocalyxone A (100, 200 mg) was evaluated against four bacterial species, namely Staphylococcus aurous, Escherichia coli, Aspergillus niger and Aspergillus flavus. Escherichia coli showed the highest susceptibility to this compound. The oral dose of oncocalyxone A at a 200mg/kg exhibited analgesic and anti-inflammatory activities in comparison with standard drug Morphine sulphate at a dose of 5 mg/kg and Diclofenac sodium at a dose of 100 mg/kg respectively. The methanolic extract of Prenanthes sarmentosus, exhibited a weak anti-bacterial, analgesic and anti-inflammatory activities in comparison with isolated oncocalyxone A. The oncocalyxone A at dose of 200mg/kg showed highly significant activities as compared to standard drugs.
Keywords: Oncocalyxone A, Prenanthes sarmentosus, anti-bacterial, analgesic activity, anti-inflammatory activity